Gamma irradiation induced clastogenic abnormalities in Vigna radiata - Lyena Watty Zuraine Ahmad,; Nur Alya Nabilah Azis,; Norfatimah Mohamed Yunus,; Azhar Mohamad, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Gamma irradiation is an effective and widely used method in the agricultural sector to alter the traits of plants especially for commercialization purposes and as a mitigation measure to ensure food security in the future. Vigna radiata (mung bean) is one of the most important legume crops in Asian countries that is not fully exploited. Therefore, this research aimed to determine the effects of gamma irradiation on the cytology and growth of mung beans. The mung bean seeds were exposed to different doses of gamma radiation; 0, 200, 400, 600, 800, and 1000 Gy. The increasing dose of gamma irradiation caused an insignificant decrease (p>0.05) in the mitotic index of V. radiata meristematic cells. However, a significant increase at p<0.05 in the percentage of clastogenic chromosomal aberration was observed in the meristematic cells of plants irradiated at 800 and 1000 Gy. The survival percentage, plant height, and root length were inversely proportional to the percentage of chromosomal aberration and clastogenic abnormalities when the irradiation dose exceeded the LD50 (752.50 Gy). In conclusion, gamma rays greatly induced clastogenic abnormalities which have varying impacts on the cytology and growth of V. radiata plants.